The Evolution of Agricultural Trade Flows - M.Ataman Aksoy; Francis Ng (Turkish Economic Association, 2013)
Earlier research showed that during the 1980s and 1990s most of the global agricultural trade expansion took place among the industrial countries and among countries within trade blocs. These were also periods of declining agricultural prices. These prices increased during the 2000s, there were continuous trade reforms, and many developing countries started to support their agricultural sectors. This paper analyzes trade flows during the past two decades, and tries to measure whether all these developments have changed the trade balances and the share of different groups within the global trade flows. In addition, it looks at the trade balances on food to see the impact of these changes on net food importing countries. In conclusion, unlike the case with manufacturing, developing countries have not been able to increase their export shares in agriculture as significantly. They have maintained their trade shares by primarily expanding exports to other developing countries.
Keywords: F01; F10; F13; Q17; Q18; 330; agriculture; agricultural trade; agricultural prices; agricultural growth; net food exporters and importers; Agraraußenhandel; Agrarpreis; Welt